Microbiological, lipid and immunological profiles in children with gingivitis and type 1 diabetes mellitus - Cristiane DUQUE; Mariana Ferreira Dib JOÃO; Gabriela Alessandra da Cruz Galhardo CAMARGO; Gláucia Schuindt TEIXEIRA; Thamiris Santana MACHADO; Rebeca de Souza AZEVEDO; Flávia Sammartino MARIANO; Natália Helena COLOMBO; Natália Leal VIZOTO; Renata de Oliveira MATTOS-GRANER
Abstract Objective The aim of this study was to compare the prevalence of periodontal pathogens, systemic inflammatory mediators and lipid profiles in type 1 diabetes children (DM) with those observed in children without diabetes (NDM), both with gingivitis. Material and methods Twenty-four DM children and twenty-seven NDM controls were evaluated. The periodontal status, glycemic and lipid profiles were determined for both groups. Subgingival samples of periodontal sites were collected to determine the prevalence of periodontal microorganisms by PCR. Blood samples were collected for IL-1-β, TNF-α and IL-6 analysis using ELISA kits. Results Periodontal conditions of DM and NDM patients were similar, without statistical differences in periodontal indices. When considering patients with gingivitis, all lipid parameters evaluated were highest in the DM group; Capnocytophaga sputigena and Capnocytophaga ochracea were more prevalent in the periodontal sites of DM children. "Red complex" bacteria were detected in few sites of DM and NDM groups. Fusobacterium nucleatum and Campylobacter rectus were frequently found in both groups. Similar levels of IL-1-β, TNF-α and IL-6 were detected in DM and NDM children. Conclusion Clinical and immunological profiles are similar between DM and NDM children. The presence of Capnocytophaga sputigena and Capnocytophaga ochracea were associated with gingivitis in DM children.